Mechanism for the Development of Medicinal Herbs from Cannabis to Enhance the Community-based Economy to Commercialization for Community Enterprises Phetchaburi Province - Tongyam, Phuntip; Tongyam , Terdsak (Journal of Applied Economics and Management Strategy [eISSN 2985-1408], 2024)
This research has purposes to: 1) manage knowledge, transfer planting and requesting permission to grow cannabis for community enterprises; 2) develop herbal pharmaceutical products from cannabis to enhance the grass-root community economy towards commercialization for community enterprises; 3) determine a driving mechanism for the community enterprise network producing herbal pharmaceuticals from cannabis to boost the grass-root community economy towards commercialization in Phetchaburi Province. The study employed a qualitative research method that collected the data through a multiple focus-group process participated by 15 people; including in-depth interviews with 9 key informants and examining the community enterprise groups growing and processing vegetables and herbs in Tha Yang District, Phetchaburi Province. The data were categorized with content analysis. It was found that the cannabis strains suitable for growing to produce commercial products from its leaves is the KD Koh Tao because it is a mixed strain that grows well and is suitable for the target area. Planting the cannabis was done after the cannabis was withdrawn from the list of the Thai Controlled Narcotic Drugs Act on June 9, B.E.2665. Growing the cannabis for commercial production could be done by registering to establish a community enterprise under the notification and registration of Food and Drug Administration, Thailand. Developing cannabis products to enhance the grass-root community economic toward commercialized community enterprises could be done by processing products from the cannabis leaves in forms of drinks for health and recreation. From examining the community enterprise network, it was found that the practice that made the community enterprise strong and sustainable consisted of participatory process in brainstorming and planning to strengthen their knowledge, marketing, and receiving mutual benefits.